Working Against Gender-Based Violence in the American South: An Analysis of Race, Ethnicity, Gender, and Sexuality in Advocacy. (November 2021) - Cayir, Ebru; Spencer, Mindi; Billings, Deborah; Hilfinger Messias, DeAnne K.; Robillard, Alyssa
Non-profit organizations that address gender-based violence must create diverse, inclusive, and equitable workplaces for advocates so that they can adequately serve diverse survivors. Despite recent efforts, differential treatment and high turnover among minority advocates continue. Further strategies to eliminate discriminative organizational practices are needed. We interviewed 25 advocates employed by non-profit organizations in a Southeastern state to examine how race, ethnicity, gender, and sexuality shape their work experiences. Guided by constructivist grounded theory and intersectionality, data analysis yielded four major themes that covered white dominance in advocacy, essentialized womanhood and heteronormativity, serving communities of color, working in the Deep South. Patriarchal values, religious norms, and gender roles influenced how advocates' work was received by the communities. Racial/ethnic minority, and sexual and/or gender minority advocates faced discrimination, tokenism, and negative stereotypes. Transforming organizational climate and policies is necessary to support minority advocates' work engagement and ability to serve marginalized communities.